AUSTRALIA DALAM BINGKAI KOLONIALISASI DAN KETERLIBATANNYA DALAM PERANG DUNIA. - Arviansyah, Muhammad Reza; Hudaidah, Hudaidah; Pahlepi, Muhammad Reza (Danadyaksa Historica, 2023)
Australia is a country as well as a continent, a country consisting of these states when compared to other continents is certainly inferior in terms of area. Australia is the smallest continent but behind the various advances and achievements they were able to achieve there is a very interesting historical record. Therefore, this paper will try to discuss Australia which is seen from the colonial period to the outbreak of world-level conflicts which are also known as world wars. Because previous studies have not discussed colonialisation in australia and australia's involvement in the world war which certainly caused various impacts. Using qualitative research methods, this paper will try to discuss and reveal the initial conditions during the colonialization period that had occurred in Australia and will also discuss the turmoil of the world war that was also felt for the Australian government at that time. In practice, this qualitative data collection is carried out by collecting various existing sources and then analyzing the various sources that have been found to ensure the compatibility between the theme to be raised and the content of the writing contained therein.